Politik Islam: Analisis Pemikiran Ibn B?jjah Dalam Kit?b Tadb?r Al-Mutawahhid - Abdul Kohar (UIN Mataram, 2020)
Ibn B?jjah was the first Muslim philosopher in Spanish. His full name is Ab? Bakr Muhammad ibn yahya al-Sh?'igh al-Tuj?b? al-Saraqust?. Ibn B?jjah is also known by the laitin name Avempace, he is a rationalist philosopher. Many of his ideas about political, especially in the book of Tadb?r al-Mutawa??id. Ibn B?jjah said that a government have to be mutawa??id, and mutawa??id should be able to control themselves and be able to control lust, not to be dragged into the mainstream of society. The purpose of this research first the writer wants to say that the government (leader) is a transformation for his society, then democratic systems isn’t just saying